Candida blankii: an emerging yeast in an outbreak of fungaemia in neonates in Delhi, India. (May 2020) - Chowdhary, A.; Stielow, J.B.; Upadhyaya, G.; Singh, P.K.; Singh, A.; Meis, J.F.
Abstract: Objective: Outbreaks of fungal sepsis due to emerging and rare multidrug-resistant Candida species are increasingly reported in health-care settings. We report an outbreak of fungaemia due to the rare multidrug-resistant yeast Candida blankii in an Indian neonatal unit. Materials and methods: Blood cultures grew C. blankii in nine neonates in the Neonatal Intensive Care Unit of a multispecialty hospital in Delhi during a period of 7 months. Isolates were identified by internal transcribed spacer and D1/D2 region sequencing. Antifungal susceptibility testing was performed by M27-A3 CLSI broth microdilution. To determine genetic relatedness among C. blankii isolates we undertook amplified fragment length polymorphism analysis and DNA sequencing using the Illumina NextSeq500 platform. Results: Candida blankii fungaemia occurred at 2–3 postnatal days in nine low birthweight/very low birthweight neonates. All neonates were treated with fluconazole and four of the nine neonates died, resulting in a case fatality rate of 45%. Candida blankii was misidentified or not identified by automated identification systems. Fluconazole had higher geometric mean (GM) MICs (8 mg/L) than the other azoles. Also, anidulafungin (GM-MIC 2 mg/L) had high MICs. Genome sequencing confirmed transmission of genetically mostly indistinguishable strains. The C. blankii genome showed an altered 1, 3-β-d -glucan synthase protein and several larger deletions in the echinocandin target FKS1 gene, suggesting potential for development of antifungal resistance. Conclusions: The study emphasizes the emergence of a rare and uncommon yeast, C. blankii, with reduced susceptibility to one or more antifungal agents, in nosocomial fungaemia. Genomic insights of this rare yeast are reported using whole-genome sequence typing.